Fingerprinting of cerrado species based on cork lipophilic constituents - Salatino, Antonio; Ferreira, Marcelo J. P.; Udulutsch, Renata G. [UNESP]; Palacios, Carmen E.; Salatino, Maria Luiza F. (Elsevier B.V., 2020)
Cerrado is a savanna ecosystem of central and southeastern Brazil. Many woody species of cerrado have thick layers of cork. The present work aimed to characterize, by GC/MS analysis, the constituents of n-hexane extracts from the cork of common species from cerrado. Cork samples from 31 individuals, corresponding to 14 species and six families, were analyzed. Similarities and differences were noticed between cork and cuticular waxes regarding profiles of lipophilic constituents. The distribution of cork constituents was analyzed using the UPGMA clustering method and DICE coefficient. All clusters in the dendrogram obtained comprise individuals from a same species, suggesting that the distribution of lipophilic cork constituents is useful for species characterization and possibly also for species identification, resembling results commonly obtained with molecular markers. Seven samples of Bignoniaceae, corresponding to two genera and seven species, emerged in a common cluster, in an arrangement in accordance with the recent segregation of Tabebuia species to a new genus Handroanthus. The markers analyzed were not efficient regarding characterization of other families.
Keywords: Fatty acids; Triterpenoids; Phytosteroids; Cerrado; Cork; Chemical fingerprinting